The study on factor that influence sustaining equity growth and value creation through intrapreneur venture of Sindora Berhad / Azmil Majid - Majid, Azmil (Faculty of Business and Management, 2010)
This report is aim to investigate whether the shift into Intrapreneur Venture as a new core business is indeed for the better and effective in enhancing Group performance or not. The IV concept involves an equity acquisition where the intrapreneurs are expected to continue spearheading and growing their businesses. Sindora, as a public listed company, will provide the institutional support, accessibility to financial instruments, and other corporate resources it is capable of rendering. This report also is aim to find out whether the claims made by the corporate sector while going for M&As to generate synergy, are being achieved or not while going for mergers and acquisitions (M&A) management smell financial synergy or/and operating synergy in different ways.